Factors associated with COVID-19 pandemic induced post-traumatic stress symptoms among adults living with and without HIV in Nigeria: a cross-sectional study - Morenike Oluwatoyin Folayan; Olanrewaju Ibigbami; Maha ElTantawi; Giuliana Florencia Abeldaño; Eshrat Ara; Martin Amogre Ayanore; Passent Ellakany; Balgis Gaffar; Nuraldeen Maher Al-Khanati; Ifeoma Idigbe; Anthonia Omotola Ishabiyi; Mohammed Jafer; et al. (United Kingdom, 2022)
Background: Nigeria is a country with high risk for traumatic incidences, now aggravated by the COVID-19 pandemic. This study aimed to identify differences in COVID-19 related post-traumatic stress symptoms (PTSS) among people living and not living with HIV; to assess whether PTSS were associated with COVID-19 pandemic-related anger, loneliness, social isolation, and social support; and to determine the association between PTSS and use of COVID-19 prevention strategies.
Methods: The data of the 3761 respondents for this analysis was extracted from a cross-sectional online survey that collected information about mental health and wellness from a convenience sample of adults, 18 years and above, in Nigeria from July to December 2020. Information was collected on the study's dependent variable (PTSS), independent variables (self-reported COVID-19, HIV status, use of COVID-19 prevention strategies, perception of social isolation, access to emotional support, feelings of anger and loneliness), and potential confounder (age, sex at birth, employment status). A binary logistic regression model tested the associations between independent and dependent variables.
Results: Nearly half (47.5%) of the respondents had PTSS. People who had symptoms but were not tested (AOR = 2.20), felt socially isolated (AOR = 1.16), angry (AOR = 2.64), or lonely (AOR = 2.19) had significantly greater odds of reporting PTSS (p < 0.001). People living with HIV (AOR = 0.39), those who wore masks (AOR = 0.62) and those who had emotional support (AOR = 0.63), had lower odds of reporting PTSS (p < .05).
Conclusion: The present study identified some multifaceted relationships between post-traumatic stress, HIV status, facemask use, anger, loneliness, social isolation, and access to emotional support during this protracted COVID-19 pandemic. These findings have implications for the future health of those affected, particularly for individuals living in Nigeria. Public health education should be incorporated in programs targeting prevention and prompt diagnosis and treatment for post-traumatic stress disorder at the community level.